Flubendazole and mebendazole impair migration and epithelial to mesenchymal transition in oral cell lines. (25th September 2018) - Kralova, Vera; Hanušová, Veronika; Caltová, Kateřina; Špaček, Petr; Hochmalová, Martina; Skálová, Lenka; Rudolf, Emil
Abstract: Benzimidazole anthelmintics flubendazole and mebendazole are microtubule-targeting drugs that showed considerable anti-cancer activity in different preclinical models. In this study, the effects of flubendazole and mebendazole on proliferation, migration and cadherin switching were studied in a panel of oral cell lines in vitro . Both compounds reduced the viability of the PE/CA-PJ15 and H376 oral squamous carcinoma cells and of the premalignant oral keratinocytes DOK with the IC50 values in the range of 0.19–0.26 μM. Normal oral keratinocytes and normal gingival fibroblasts were less sensitive to the treatment. Flubendazole and mebendazole also reduced the migration of the PE/CA-PJ15 cell in concentrations that had no anti-migratory effects on the normal gingival fibroblasts. Levels of the focal adhesion kinase FAK, Rho-A and Rac1 GTPases and the Rho guanine nucleotide exchange factor GEF-H1 were decreased in both PE/CA-PJ15 cells and gingival fibroblasts following treatment. Both drugs also interfered with cadherin switching in the model of TGF-β-induced epithelial to mesenchymal transition (EMT) in the DOK cell line. Levels of N-cadherin were reduced in the TGF-β induced cells co-treated with flubendazol and mebendazole in very low concentration (50 nM). These results suggest direct effects of both benzimidazoles on selected processes of EMT in oral cell lines such as cadherin switching as well as cellular migration. Highlights: Flubendazole and mebendazole impaired migration of squamous carcinoma cells, but not normal cells. Both drugs interfered with cadherin switch in the model of TGF-β-induced EMT. N-cadherin level was reduced in TGF-β-induced cells treated with 50 nM flubendazole or mebendazole.